For this system of equation I used substitution:
Step 1: Every time you see a y in the equation y = 2x - 1 replace it with -4x - 19
-4x - 19 = 2x - 1
Step 2: Isolate x
(-4x + 4x) - 19 = (2x + 4x) - 1
-19 = 6x - 1
-19 + 1 = 6x + (- 1 + 1)
-18 = 6x
x = -3
Step 3: To solve for y replace x in the equation y = 2x - 1 with -3
y = 2(-3) - 1
y = -6 - 1
y = -7
(-3, -7)
Check:
-7 = -4(-3) - 19
-7 = 12 - 19
-7 = -7 --------------------------------> Correct!
-7 = 2(-3) - 1
-7 = -6 - 1
-7 = -7 --------------------------------> Correct!
Hope this helped!